Dampak Plagiarisme Terhadap Penulisan Artikel Ilmiah - Gusnayetti, Gusnayetti (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
Plagiarism can damage the credibility and reputation of the author, and can also result in the withdrawal of articles, disciplinary sanctions, and legal action. In the academic world, plagiarism can threaten a student's graduation and a lecturer's academic career. The term plagiarism has entered various disciplines and fields of life as a form of violation of intellectual ethics. Writing is a skill that cannot be obtained quickly and instantly because it requires a long process and time. The more time spent writing scientific articles, the more experience and knowledge will be gained about writing scientific articles. A scientific article is a writing that contains ideas, thoughts and thoughts from a person or group of people through a research or non-research process that is expressed in the form of a written report by observing certain systematics, methods and rules so that its truth can be tested. The impact that can occur due to plagiarism is that it can damage both the individual and the institution. One of the requirements for a good and quality scientific article must be able to provide benefits or contributions to science. The contribution in question is like producing a new theory or perfecting previous theories. Researchers need to pay attention to all parts of writing scientific papers with full care and responsibility.